2018
DOI: 10.4108/eai.13-7-2018.163980
|View full text |Cite
|
Sign up to set email alerts
|

Using Hadamard transform for cryptanalysis of pseudo-random generators in stream ciphers

Abstract: In this work we discuss results obtained from an application of the Hadamard transform to cryptanalysis, and in particular, we determine the probability to decipher different pseudo-random number generators used as components of stream ciphers. Also, we found a relationship between entropy and Hadamard's values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Guillermo Sosa-Gómez et al [91] showed the cryptanalysis of PRNGs for cryptographic ciphers. Also, a correlation analysis of the entropy of PRNGs and Hadamard values indicate a strong correlation.…”
Section: Open Research Problemsmentioning
confidence: 99%
“…Guillermo Sosa-Gómez et al [91] showed the cryptanalysis of PRNGs for cryptographic ciphers. Also, a correlation analysis of the entropy of PRNGs and Hadamard values indicate a strong correlation.…”
Section: Open Research Problemsmentioning
confidence: 99%
“…These two criteria measure different characteristics of the change's effect that an input bit has on the output bits; while the SAC verifies uniformity in the distribution of each output bit, the BIC measures the degree of independence between the output bits [15]. The SAC has been extended to be applied to stream ciphers [16][17][18][19][20][21][22]. In [22], the RC4 stream cipher [23] was evaluated through the SAC and the existence of statistical dependence between the input bits and outputs of the RC4 was detected for inputs of large size.…”
Section: Introductionmentioning
confidence: 99%